The Problem of the Location of the Gabuleum and Theranda road stops on the Lisus–Naisus Roman road (Upper Moesia) - Samardžić, Gligor (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The paper presents data on the problem related to the location of Gabuleum and Theranda road stops on the Lisus–Naisus Roman road (Upper Moesia). The Lisus–Naisus Roman road intersected modern-day Kosova and Metohija stretching from the southwest to the northeast. The road, being the main road, connected the seaside to the inland. Not a considerable number of milestones, i.e. their fragments, was found on this part of the road. They are of significan historic value due to the fact that they represent genuine evidence of the existence of the Roman road in Kosovo and Metohija. During the research of ancinet road stops and roads in the south of the province of Upper Moesia (Kosovo and Metohija), we used written sources and material remains on the terrain for which the data from Tabula Peutingeriana and Ptolemy’s Geography were highly significant. The epigraph statues are equally important, i.e. milestones, road remains, settlements and other material remains.Their more detailed study and research can provide researchers with the opportunity to point to the main road routes, road stops and settlements in this area. The question of the location of Gabuleum road stop stays open due to the fact that the researchers have not reached a consenus till today on its location because, as previously mentioned, there have been many opinions. The prevelant opinion in the contemporary scientific circles, being based on Tabula Peutingeriana, is that Gabulem should be looked for near the place called Kukës in Albania where the White and Black Drim converge. By quoting Tabula Peutingeriana, the traces of the Roman presence as well as the unsafe road route to the north, the location of Therande is linked to the territory of Metohija, near the places such as Suva Reka or Ljubižda, in the valley of the Miruša river, not far from Prizren.